kecernaan jerami padi fermentasi dengan probiotik starbio terhadap domba jantan lokal - gema pirngadi gultom (Jurnal Peternakan Integratif, 2013)
ABSTRACT GEMA PIRNGADI GULTOM, "Digestibility Rice Straw Fermented by Probiotics Starbio to Local Male Sheep" Guided by TRI Hesti WAHYUNI and NEVY DIANA HANAFI. The experiment was conducted at the Faculty of Agriculture, University of North Sumatra in April 2012 - October 2012. Rice straw fermentation by probiotok Starbio can increase consumption, digestibility of dry matter and organic matter. This study aimed to determine the effect of the level of utilization of rice straw fermented with probiotok Starbio the digestibility of dry matter and organic matter digestibility local sheep ram. The design used in this study is a Latin square design (RBSL) with 4 treatments and 4 replications. Treatment consists of P0 (unfermented rice straw), P1 (0.4 kg + 0.4 kg urea Starbio / 100 kg rice straw), P2 (0.6 kg + 0.6 kg urea Starbio / 100 kg rice straw) and P3 (0.8 kg + 0.8 kg urea Starbio / 100 kg rice straw). The results showed the average dry matter intake (g / head / day) 467.06; 465.72; 489.52 and 481.1 respectively. Average consumption of organic material (g / head / day) 391.49; 391.05; 412.92 and 403.65 respectively. Mean dry matter digestibility 47.57; 46.59; 50.07 and 49.17 respectively. Mean organic matter digestibility 83.59; 80.32; 81.90 and 82.56 respectively. Statistical analysis showed that administration of different levels of fermented rice straw probiotok Distinct Starbio no significant effect on consumption of dry matter, organic matter intake, digestibility of dry matter and organic matter digestibility local sheep ram. Keywords: Digestibility, rice straw, fermentation and local sheep ram Starbio